ZINC OXIDE NANOPARTICLES INHIBIT SOME FUNGAL PATHOGENS INFECTION ON DURIAN SEEDLINGS - Kongtragoul, Pornprapa; Pantakan, Miss Sansanee (My University, 2024)
Durian disease-causing organisms such as fungi can infect durian trees at any stage of development. Chemical fungicides are widely used because they are convenient and simple to use. However, it impacts the health of producers, consumers, and the environment. As a result, recommendations have been developed and established for researching zinc oxide nanoparticles (Zn-ONPs) that can inhibit fungal growth as an alternative for preventing and eliminating such fungi. The purpose of this study is to collect and isolate some fungi that cause durian diseases and their pathogenicity test, as well as to investigate the efficacy of Zn-ONPs ranging in size from 25 to 50 nm in inhibiting germination and fungal infection on durian seedlings. Three isolates of Phytophthora sp. (CL4_F1, CL4_S5, CL4_F10), two isolates of Fusarium sp. (CL6_FL1, CL6_FL2), two isolates of Phomopsis sp. (CH1_PF1, CH1_PF2), and two isolates of Rhizoctonia sp. (CL1_RL1, CL1_RL2) were successfully isolated as durian pathogenic fungi. All isolates were pathogenic on durian seedlings, with a 100% disease incidence. As a result, it was found that increasing the concentration of ZnO-NPs could further inhibit growth in the germination and infection of durian seedlings. All tested isolates had delayed germination by ZnO-NPs at all concentrations. Furthermore, as the severity of the disease decreased, ZnO-NPs could inhibit infection in durian seedlings at higher concentrations.
Keywords: durian diseases; Fusarium sp; Phomopsis sp; Phytophthora sp; Rhizoctonia sp; zinc oxide nanoparticles